Exploitation yield of trawl in Kien Giang province from 2014 to 2015 - Hai, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
In periods from July 2014 to June 2015, the Research Institute for Marine Fisheries collected data about yield from catch landing of the trawl fisheries in Kien Giang province. Total yield was calculated by Stamatopoulos Constantine’s method in 2002. The results indicated that the total yield of trawls in Kien Giang province was about 592.5 thousand tons one year. In which, the pair trawl’s yield was 84%, the otter trawl’s yield was 16%. The yield structure was different between pair trawl and otter trawl. Main yield components of pair trawl were trashfish and anchovy groups; and those of otter trawl were trashfish, mixed fish and mixed shrimp.